Tindak Pidana Zina Perspektif Qonun Jinayah Aceh - Alfidh Ardiansyah; Ari Hardiansyah; Catur Intan Nuriah Nurbani Yazid; Deni Baskara; Deden Najmudin (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The act of adultery occurring today is attributed to the decline in moral values within society. Free sex is one example, where individuals engage in sexual relations without rules. We aim to discuss adultery from the perspective of Aceh's criminal law, exploring the definition, historical background, and the implementation of the punishment for adultery. The objective is to delve into the understanding of criminal law, introduce the early history of Aceh's law, and comprehend the application of adultery punishment within Aceh's legal framework. The research methodology for examining adultery in the context of Aceh's criminal law involves a qualitative approach, relying on literature, both primary and secondary data, specifically related to Article 33 on adultery. The data collection method is through library research. This study follows the Qanun Jinayat research method, where all forms of law and formal rules originate from Islamic Sharia applied in Aceh. The research aims to understand the concept of adultery, its types, and violations from the perspective of Aceh's criminal law. The overall findings suggest that, based on the analysis, criminal acts of adultery in Aceh's Qanun encompass various types of actions, each with distinct sanctions. This study aims to inform the public about adultery offenses and their corresponding penalties, fostering a better understanding to avoid not only the punishment but also the consequences in this world, as outlined in Aceh's criminal law.